Not Just "Sustainable": Communicating Growing Practices in a Statewide - Gretchen Perbix (Journal of Applied Communications, 2014)
While food texts like labels and descriptions are considered persuasive, few are written by growers themselves, and thus growers have infrequent opportunities to influence consumers through written communication. This study seeks to discover how retail growers frame descriptions of themselves in a print and online directory. The study employed a qualitative textual analysis of 406 growers’ 460-character directory listings to identify how they frame themselves and distinguish their operations from others’ operations. Results indicate growers predominantly use three frames: a product frame, a process frame, and an experience frame. Frames are sometimes used in combination with each other, and some growers use particular frames intensively. Both practices provide differentiation opportunities for growers. Growers of the same type tended to use the same type of frame, so growers seeking differentiation opportunities could use frames not commonly used by growers of their type. Since growers are not often professional communicators, agricultural communicators and extension educators can use the findings from this study to help educate growers about how to communicate about their operations.
Keywords: Framing theory; textual analysis; grower-authored directory listings